Insights into the genetic and metabolic engineering approaches to enhance the competence of microalgae as biofuel resource: A review. (November 2021) - Brar, Amandeep; Kumar, Manish; Soni, Twinkle; Vivekanand, V; Pareek, Nidhi
Highlights: Microalgal engineering to enhance proficiency as biofuel resource. Comprehensive account on algomics for enhanced lipid production. Shifts in metabolic flux could alter the algal physiology and lipid generation. Intervention of genetic and metabolic switches boost algae-based biofuel production. Abstract: Conventional fuel resources are overburden with speedy global energy demand which ensued the urgent need of alternate energy resources. Biofuel generation efficiency of microalgae is notable due to their comparatively rapid biomass production rate and high oil content. But, the employment of microalgae as biofuel resource is in infancy due to low productivity and high production cost. The issues can be addressed by employing engineered microalgal strains that would be able to efficiently generate enhanced levels of biomass with augmented lipid and/or carbohydrate content for proficient biofuel production. Genetic alterations and metabolic engineering of microalgal species might be helpful in developing high stress-tolerant strains with improved properties for biofuel generation. Various omics approaches appeared significant to upgrade the microalgal lipid production. Intervention of genetic and metabolic engineering approaches would facilitate the development of microalgae as a competent biofuel resource and inflate the economic commercialization of biofuels.